Trevor Mann (1916–1996): Paediatrician responsible for the development of hospital services for children in Brighton, England. (May 2023) - Patterson, Rosemarie; Sornalingam, Sangeetha; Cooper, Maxwell John
Trevor Philip Mann (1916–1996) was the first consultant paediatrician at the Royal Alexandra Children's Hospital (RACH) in Brighton, since its foundation in 1881. Here, he was responsible for significant service developments, including establishing a department of paediatric surgery and the first neonatal unit in England outside of London. Mann grew up in South London, and aged 14 had a lengthy admission to hospital with tuberculosis. He studied medicine at St Mary's Hospital, London. During World War II he was a Royal Navy Surgeon-Lieutenant, aboard the Atlantic destroyer, HMS Georgetown, and with the Russian convoys, before completing paediatric training in London. Here, he was involved in treating paediatric tuberculous meningitis; clinical work that formed part of one of the earliest randomised controlled trials. In 1951 Mann moved to the RACH where he researched infantile infectious gastroenteritis and introduced (now commonplace) practices at the hospital, including barrier nursing. He lived in Rottingdean, Sussex, and enjoyed sailing, gardening and wood turning. Mann's impact on paediatric care in Brighton was recognised by the hospital, naming the Trevor Mann Baby Unit in his honour, upon his retirement in 1981. This article seeks to record his contributions and reconnect local clinicians with his memory.